Human resource costing review of literature and strategies for implementation - Abdul Majid, Abdul Halim (Penerbit Universiti Utara Malaysia, 2010)
Most modern HR practitioners would generally agree that the people in their organization are valuable assets and are as important, if not more important, than the organization’s physical and intangible assets. The HR (people) assets have been recommended to be measured and linked to accounting reporting mode. Such mode or a discipline that measures human assets and activities is called the Human Resource Costing (HRC). The first part of this monograph highlights previous literatures in explaining concepts, justifications and potential challenges in implementing HRC. Meanwhile, the second part offers some strategies and examples in measuring costs for selected HR elements such as on-line selection, turnover, staff development, strike, accidents at workplace, interviews and absenteeism. Notes related to the Balance Scorecard (BSC), as a tool to support HRC implementation indicates a way forward where a framework that translates vision and strategy into financial and non-financial aspects are made toward the end of this monograph.